2010
DOI: 10.1530/rep-08-0377
|View full text |Cite
|
Sign up to set email alerts
|

NAMPT (visfatin) in the chicken testis: influence of sexual maturation on cellular localization, plasma levels and gene and protein expression

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) is a cytokine hormone and rate-limiting enzyme involved in production of NAD and therefore affects a variety of cellular functions requiring NAD. Spermatogenesis and testicular steroidogenesis are likely to depend on NAD-dependent reactions and may therefore be affected by changes in testicular NAMPT expression. The objectives of the present study are to investigate testicular NAMPT expression as well as plasma NAMPT levels in prepubertal and adult chickens. By RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…NAMPTA has been reported in different vertebrate lineages such as fish , birds and mammals , although nothing is known about the presence of NAMPTB. In the present study, the origination, evolution and functions of NAMPTB were analyzed for the first time in vertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…NAMPTA has been reported in different vertebrate lineages such as fish , birds and mammals , although nothing is known about the presence of NAMPTB. In the present study, the origination, evolution and functions of NAMPTB were analyzed for the first time in vertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, we report for the first time the presence of NAMPT in human spermatozoa. In this study, the expression pattern of NAMPT was similar to the results found in chicken testis (Ocón‐Grove et al ., ). In detail, NAMPT was detectable in spermatogonia, spermatocytes, Sertoli and Leydig cells.…”
Section: Discussionmentioning
confidence: 97%
“…NAMPT concentrations in seminal plasma were nearly 100‐fold higher than that measured in serum (Thomas et al ., ). NAMPT protein has been detected in chicken spermatocytes, spermatids and seminal plasma (Ocón‐Grove et al ., ). We hypothesise that NAMPT is also present in human testes and spermatozoa.…”
Section: Introductionmentioning
confidence: 97%
“…Given the role of salvage biosynthesis in the maintenance of NAD + levels and its importance in general metabolism, it came as a surprise that neither expression of Nampt in mice nor nicotinamidases in Drosophila and C. elegans is ubiquitous (Chintapalli et al, 2007; Revollo et al, 2007b; Vrablik et al, 2009). Like C. elegans, which encodes a secreted PNC-1 isoform, vertebrates express an intracellular (iNampt) and extracellular (eNampt) (Yonezawa et al, 2006; Revollo et al, 2007a; Ocón-Grove et al, 2010). NAD + biosynthetic capacity might be provided to tissues that lack Nampt or nicotinamidase expression by cell-autonomous expression of enzymes in other NAD + biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%